Analysis of the Implementation of Waqf Wasiar Sharia Insurance Policies in Review from Islamic Law - Azizah Rahmah; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
This study aims to analyze the implementation of waqf testaments for sharia insurance policies. Based on the Fatwa DSN MUI variation 106/DSN-MUI/X/2016 concerning the Benefits of Waqf Insurance and Funding Benefits in Sharia Life Insurance, it is regulated that the challenge for assets that may be waqf is 45% while in Waqf law it is 1/3 of wealth or Syirkah. This study uses a qualitative technique by using a literature study. The results of this study indicate that the implementation of waqf wills in sharia insurance policies has not been fully implemented and well controlled..